Decoding The Hidden Semiotic Meaning of the Pepsi Advertisement Logo - Wardana, I Ketut (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2025)
The representamen of Pepsi advertisements' logo comprises a circular shape in red, blue, and white, adorned with curved lines. Nevertheless, the interpretant derived from this logo is not always transparent or consistent, owing to the diverse perspectives, experiences, cultures, and contexts of individuals. Hence, this study investigated the semiotic meaning encapsulated within the Pepsi logo from a cultural standpoint. This study employed a qualitative interpretative approach to grasp the significance and contextual implications embedded within these visuals. Pepsi’s logos from different decades were observed, including the use of colour, shapes, and selections of words. The data were analysed using Peirce's semiotic theory. The findings revealed that the form, function, and meaning of the Pepsi logo were decoded through ten distinct types of sign vehicles, their objects, and interpretants. However, a majority of these interpretations were culturally conventional. The choice of vertical or horizontal arrangement of the PEPSI typography, colors, and lines was interpreted as representative of a cultural system encompassing both individualism and collectivism. Although there seems to be a lack of an iconic relationship with the represented object and an imbalance between consistent representamen and varied interpretants, the semiotic analysis research conducted on the Pepsi logo holds positive implications for the advancement of linguistics and effective marketing strategies.